The Effect of the Experimentally Induced Hypothyroidism on Thymus of Different Aged Rats - Kükner, Aysel; Öner, Jale; Çolakoğlu, Neriman; Canpolat, Leyla; Ozan, Enver; Ozan, Sema (Fırat University, 2001)
Thyroid gland hormones influence thymic structure. The outflow of T cells the thymus is reduced in thyroid hypofunction. In this study, experimental hypothyroidism was induced in 30, 45 and 60 days old female rats by intraperitoneally injections of propilthiouracil (10mg/kg day). In the light and electron microscopic investigation, the different thymic influence were observed among age groups. The thymic weight of experimental groups were lower than controls. The apoptotic lymphocytes, macrophages which phagocytosed apoptotic bodies, plasma cell and eosinofil around blood vessel, dilated vessels in the gland and septum, mast cells which increased as number in septum were determined in the thymic structure. Catalase activity and G-6-PD activity in plasma were decreased while malonaldehyde (MDH) activities in plasma and tissue was increased. The drugs which lead to hypothyroidism caused involution in thymus, this involution was occured extremely in adult group.

Tiroid bezi hormonları timus yapısını etkilemektedir. Tiroid hipofonksiyonunda timustan perifere T lenfositlerin çıkışı azalmaktadır. Bu çalışmada 30, 45, 60 günlük dişi sıçanlara propiltiourasil (6-n-propyl-2-thiouracil, Sigma) 10 mg/kg gün, intraperitoneal olarak verilerek deneysel hipotiroidizm oluşturuldu. Işık ve elektron mikroskopik incelemelerde, yaş gruplarındaki timus etkilenmesinin farklı olduğu gözlendi. Deney gruplarının timus bez ağırlıkları kontrol gruplarına göre anlamlı oranda daha düşüktü. Timus yapısında, apoptozise giden lenfositler, apoptotik cisimleri fagosite etmiş makrofajlar, kan damarları çevresinde plazma hücreleri ve eozinofiller, bezde ve septumda oldukça genişlemiş kan damarları ve septumda sayıca artmış mast hücreleri saptandı. Ergin olan 60 günlük grupta bu etkilenmeler en fazla idi. Plazma ve dokuda Malondialdehit (MDH) aktivitelerinde artış gözlenirken, katalaz aktivitesi ve plazmada G-6-PD aktivitesi azalmıştı. Hipotiroidizme yol açan ilaçların timus bezinde gerilemeye neden olduğu, bu gerilemenin ergin grupta daha şiddetli ortaya çıktığı görülmüştür.
DENEYSEL OLUŞTURULAN HİPOTİROİDİZMİN FARKLI YAŞ GRUPLARINDAKİ SIÇAN TİMUS BEZİNE ETKİLERİ